AMISOM and the regional construction of a failed state in Somalia. Issue 471 (14th September 2018) - Fisher, Jonathan
Abstract: Somalia, for many analysts, is the paradigmatic 'failed state', as well as the site of numerous external interventions since 1991. However, while early interventions were designed and directed by international actors, more recent peace operations have been led by regional states. The current African Union Mission in Somalia, AMISOM, has been presented by its supporters and financiers as a novel 'African solution' to a putative 'African problem'. This article seeks to challenge analyses of AMISOM and other African peace operations that contrast 'international' approaches with 'local' or 'African' approaches, focusing instead on the region as a unit of analysis. In doing so, the study uses archival and interview data to interrogate how regional politico-military elites have viewed Somalia, their role within it and the kind of political authority they have wished to see established there since the genesis of AMISOM. The article finds that regional elites have sought to use AMISOM to impose a particular version of statehood on Somalia, based in both neo-Weberian institutionalist theory and their own domestic political experiences. This has entailed not only the rejection of central manifestations of Somali political authority but also the regional construction of Somalia itself as a failed state.